Effects of a low cost levonorgestrel releasing intrauterine system on the bleeding pattern of women having menorrhagia: a phase two clinical trial. - Samarakoon, A (My University, 2008)
Women over the age of 40 years, presenting with menorrhagia without any uterine pathology were selected for the study. They underwent dilation and curettage as a mode of endometrial sampling under general anaesthesia and at the same time the 3inl-IUS was inserted in the treatment group. Control groupwas treated with Mefenamic acid after the DC. They were followed up until 3 months after the treatment. Treatment with the 3inl-IUS resulted in a significant reduction in menstrual blood loss when assessed with visual bleeding score (mean =64;SD=54vs, mean -282; SD =3.7vs. mean =8.2 days; SD2.9p=0.000). Prresence of pain in the form of dysmenorrhoea or lower abdominal pain was increased with 3inl-IUS, although it did not affect the increase in patient satisfaction which was associated with the new treatment.